Innovation of Poly(Lactic Acid)/Carbon Black Composite as an Environment-Friendly Antistatic Packaging - Andhika Talentyoadi; Monica Tashya Putri; Ivandre Ivandre; Mujtahid Kaavessina (CHEMICA: Jurnal Teknik Kimia, 2022)
Antistatic packaging mainly functions to protect an electronic device from damage caused by the electronic discharge. However, antistatic packaging is typically made with a polymer that's hard to decompose naturally, this can badly affect Indonesian environments considering Indonesian produce a lot of plastic waste. Therefore, environmentally friendly antistatic packaging could potentially alleviate several plastic wastes generated. Antistatic packaging made of Conductive Polymer Composite (CPC)  with Poly Lactic  Acid as its matrics have a biodegradable characteristic, biocompatibility, resistance to thermal and chemical influence. And the use of Carbon Black as its filler can increase the electrical conductivity of CPC. CB is synthesis by burning coconut shells and activation with H2SO4. The synthesis of CPC samples was carried out by 2 methods; melt blending using an extruder and solvent blending using chloroform solvent and stirring with a magnetic stirrer at 650 rpm at 60°C. The filler composition was varied, namely 0, 0.5, 0.1, 1.5% by weight of PLA for blending melt and 0, 1.5% by weight of PLA for blending solvent. The thermal properties of the sample were tested by DSC, it was found that the Melting Temperature of the sample was not much different from that of pure PLA with a difference of 0.4-2.2°C. With the FTIR test, it is known that the solvent has completely disappeared from the sample, and the conductivity test shows a increase in conductivity along with the addition of filler from 9,505x10-12 S/cm to 5,752x10-7 S/cm and 9,872x10-12 S/cm to 1,034x10-6 S/cm for melt and solvent method.